AB0532 Diagnostic Performance of the American-European 2002 Criteria and the Preliminary 2012 American Criteria for Primary SjÖGren Syndrome. (10th June 2014) - Gauna, M.A.; Secco, A.; Oliver, M.; Puente, D.; Scarafia, S.; Carlevaris, L.; Bennasar, G.; Marino, L.; Papasidero, S.; Barreira, J.C.; Encinas, L.; Caeiro, F.; et al.
Abstract : Background: The diversity of classification criteria for Primary Sjögren's Syndrome (pSS) makes it difficult to draw conclusions from clinical studies. The most commonly used are the 2002 American European criteria. Recently, the new 2012 preliminary criteria have been proposed. Objectives: To assess the diagnostic value of both pSS classification criteria, the American-European 2002 and the preliminary 2012. Methods: The medical expert opinion of rheumatologists from different reference centers in Argentina was considered as the Gold Standard. Sensitivity (S), specificity (Sp), positive predictive value (PPV), negative predictive value (NPV), and positive likelihood ratio (LR+) of both criteria was evaluated. Results: 100 patients were diagnosed with pSS according to expert opinion and 83 with another rheumatic disease or Sicca symptoms (AR: 31 LES: 17, Scleroderma: 3, Dermatomyositis: 2, Rhupus: 2, Undifferentiated Arthritis: 2, Psoriatic Arthritis 1, PTI: 1, Sicca: 24). 93.1% were female, with a median current age of 54 years (IQR 45-65). For the 2002 criteria: the overall sensitivity was 0.88 (0.81-0.94), the Sp: 0.89 (0.82 -0.96), the LR+: 8.07 (4.33 - 15.03), PPV 0.90 (0.83- 0.96), NPV 0.87 (0.80-0.94). For the 2012 criteria: the overall results were: for sensitivity 0.92 (0.86-0.98), Sp: 0.96 (0.92- 1), LR+: 23.67 (7.79 - 71.9), PPV: 0.96 (0.91-1), NPV 0.93 (0.87- 0.98). Conclusions: The 2012 preliminary criteria showed better performance than the American European 2002 Criteria. However, considering that most of confidence intervals overlap, these differences might not be relevant. References: Shiboski et al. American College of Rheumatology Classification Criteria for Sjögren's Syndrome: A Data-Driven, Expert Consensus Approach in the SICCA Cohort. Arthritis Care Res 2012. John P. Whitcher et al. A Simplified Quantitative Method for Assessing Kerato conjunctivitis Sicca from the Sjögren's Syndrome International RegistryAm J Ophthalmol. 2010. C Vitali et al. Classification criteria for Sjögren's syndrome: a revised version of the European criteria proposed by the American-European Consensus Group. Ann Rheum Dis 2002. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4418